Analisis Penetapan Harga Intrinsik Saham sebagai Dasar Pengambilan Keputusan Investasi dengan Menggunakan Dividend Discount Model - Nurfalika Budiarti (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to analyze the intrinsic price of stock as a basic for an investment decision making by using Dividend Discount Model. The population used in this study were all companies listed in Kompas100 Index during the period 2015-2019. Based on the purposive sampling method, 19 companies were obtained as samples in this study. Type of this study is a descriptive method with a quantitative approach. The result based on Dividend Discount Model show that BBTN, BMRI, PGAS, PWON, TLKM stocks are in undervalued condition so it is advisable to buy these stocks. ACES, BBNI, BBRI, CTRA, INTP, JSMR, KLBF, PTBA, SCMA, UNTR, UNVR, WIKA stocks are in overvalued condition so it is advisable to sell these stocks immediately. ADHI and BJTM stocks are in correctly valued condition so it is advisable to hold these stocks Keywords: Intrinsic Price; Dividend Discount Model; Investment Decision